2018
DOI: 10.1111/apt.14540
|View full text |Cite
|
Sign up to set email alerts
|

Review article: the evidence that vancomycin is a therapeutic option for primary sclerosing cholangitis

Abstract: SummaryBackground and Aims: PSC is an autoimmune biliary inflammatory disorder that is often associated with inflammatory bowel disease (IBD), with 50%-75% of patients with PSC having coexisting IBD, most commonly ulcerative colitis. Currently, no medical therapies have been shown to improve the disease course or slow its progression. However, ongoing research has resulted in a growing interest in the use of antibiotics for treatment of PSC, of which vancomycin is the most studied. In this review, we summarise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
50
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 68 publications
2
50
0
1
Order By: Relevance
“…Similar studies have not been performed in children, although short‐term biochemical improvement has been reported . Consequences of UDCA withdrawal in children with PSC are important for informing parents who may wish to discontinue the drug based on the adult study and to inform clinical trial design of UDCA studies with a control arm or any new PSC medications (e.g., vancomycin, farnesoid X receptor agonists) that would optimally be performed off UDCA …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Similar studies have not been performed in children, although short‐term biochemical improvement has been reported . Consequences of UDCA withdrawal in children with PSC are important for informing parents who may wish to discontinue the drug based on the adult study and to inform clinical trial design of UDCA studies with a control arm or any new PSC medications (e.g., vancomycin, farnesoid X receptor agonists) that would optimally be performed off UDCA …”
Section: Discussionmentioning
confidence: 99%
“…(7,16) Consequences of UDCA withdrawal in children with PSC are important for informing parents who may wish to discontinue the drug based on the adult study and to inform clinical trial design of UDCA studies with a control arm or any new PSC medications (e.g., vancomycin, farnesoid X receptor agonists) that would optimally be performed off UDCA. (13) During our study, we found that average liver biochemistries increased modestly overall with controlled UDCA withdrawal in children with quiescent PSC. Further analysis after stratification into treatment response groups showed that one third had normal ALT and GGT that remained normal in the absence of UDCA therapy (null group), one third increased above 100 IU/L (flare group), and the rest had intermediate responses (indeterminant group).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…lipopolysaccharides, LPS) also contributes by involving innate immune responses [32][33][34][35]. Furthermore, a series of studies now strongly indicate that the gut microbiota may be involved in PSC pathogenesis [17,[36][37][38][39][40] giving rise to clinical trials involving fecal transplantation, non-absorbable antibiotics, and other means of manipulating the gut microbiome in patients [17,[41][42][43]. In the bile ducts, bacterial, and fungal colonization may follow cholestasis and endothelial damage, through the establishing of a pathogenic biliary microbiota further propagating inflammation and intercurrent infections [44].…”
Section: Pathophysiological Basis Of Therapymentioning
confidence: 99%